Computer-enhanced and mobile-assisted language learning : emerging issues and trends - Zhang, Felicia (Information Science Reference, 2012)
"This book presents the latest research into computer-enhanced language learning as well as the integration of mobile devices into new language acquisition"--Provided by publisher.